Q: 6 plus z equals 3 solve for z?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

It works out that x = 6 and y = 3 or as (6, 3)

6+8=14

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

9y subtract 11 equals 7

2x+8 = 6 2x = 6-8 2x = -2 x = -1

Related questions

m= -3

minus 5

-6

(x-3)(x-2)

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

25-7=18 18/3=6

No! It equals 15, but 9-6=3.

a= -0.8

you cannot solve this without more information. When 3 variables are involved, you need 2 equations to solve for the answers for both variables.

2.5 plus 6 plus 3 equals 2.5 plus 6 plus 3

No.

It works out that x = 6 and y = 3 or as (6, 3)